Hematocrit Levels In High Work-Intensity Individuals: Study In Construction Workers - Sih Prabandari, Anggraeni; Che Azmi, Norhaida; Dwi Astiti, Erna (LPPM Universitas Duta Bangsa Surakarta, 2024)
Background: Physical activity carried out by humans causes the muscles to contract and a heat response arises in the body which is activated by the anterior hypothalamus resulting in skin vasodilation and sweating. The heat response also causes changes in the circulation of the heart and respiratory system so that the rate of metabolism in the muscles increases. This increases the dilation of blood vessels resulting in a decrease in plasma (intravascular fluid) which causes hemoconcentration and increases hematocrit levels. Construction workers have strenuous physical activity so it is possible to have a higher hematocrit level than others. Objective: This study aims were to determine the level of hematocrit in construction project workers. Method: It was descriptive analysis. The number of samples were 30 people, male sex. The sample used is blood. Hematocrit levels were analyzed with an automatic hematology analyzer. Result: 93,4% (24/30) of respondents aged 26-35 years. The result of measuring hematocrit levels found that 80% (24/30) had normal hematocrit levels, while 20% (6/30) had low hematocrit levels (hemodilution) and found no hemoconcentration. Conclusion: There is no increase in hematocrit levels in construction workers who are affected by physical activity.